Protective Effect of Atazanavir Sulphate Against Pulmonary Fibrosis In Vivo and In Vitro. Issue 2 (6th September 2017) - Song, Shina; Ji, Yunxia; Zhang, Guanghua; Zhang, Xue; Li, Bin; Li, Defang; Jiang, Wanglin
Abstract: Atazanavir sulphate, an antiretroviral protease inhibitor, has been used to treat HIV/AIDS, but its ability to serve as an antipulmonary fibrosis (PF) agent remains unknown. In this study, the effects of atazanavir sulphate on various aspects of PF were examined and CoCl2 was used to induce the hypoxia‐mimicking condition in vitro, including epithelial–mesenchymal transition (EMT) in A549 cells, endothelial–mesenchymal transition (EndMT) in human pulmonary microvascular endothelial cells (HPMECs), proliferation in human lung fibroblasts (HLF‐1) and potential protective effects in human type I alveolar epithelial cells (AT I). Additionally, the effects of atazanavir sulphate were examined using a bleomycin (BLM)‐induced pulmonary fibrosis model. After atazanavir sulphate treatment, in A549 cells and HPMECs, the expression of vimentin, HMGB1, Toll‐like receptor 4 (TLR‐4) and p‐NF‐κB decreased, while the expression of E‐cadherin and VE‐cadherin increased. In AT I cells, the expression of aquaporin 5 and RAGE were increased after atazanavir treatment. Proliferation of HLF‐1 was reduced after atazanavir treatment, meanwhile the expression of hypoxia‐inducible factor‐1α (HIF‐1α), prolyl hydroxylase domain protein 2 (PHD‐2), HMGB1, TLR‐9, p‐NF‐κB, collagen I and collagen III was decreased. In the BLM‐induced pulmonary fibrosis rat model, atazanavir sulphate ameliorated PF by reducing pathological score, collagen deposition and the expression of α‐SMA, HIF‐1α, PHD‐2, HMGB1, TLR‐4, TLR‐9 and p‐NF‐κB. In summary, our study supports the proposal that atazanavir sulphate may have a therapeutic potential in reducing the progression of pulmonary fibrosis by suppressing HMGB1/TLR signalling.